Physical mechanisms of oceanic mantle earthquakes: Comparison of natural and experimental events. Issue 1 (December 2018) - Kita, Saeko; Ferrand, Thomas
Abstract Because they provide information about the spatial distribution of brittle deformation, both seismologists and experimentalists use b-values to study earthquake populations. Here, we present the b-values for intermediate-depth intraslab earthquakes in the Pacific slab beneath the Tohoku and Hokkaido regions, northeastern Japan and find a difference in the lower-plane event b-values in the double seismic zone. Lower-plane events reveal significantly larger b-values beneath Tohoku (0.96) than Hokkaido (0.86), implying that the brittle deformation beneath Hokkaido is more localized and leads to higher ratio of relatively large lower-plane events than occur beneath Tohoku. We also estimated the b-values for experimental earthquakes, and found they increase with increasing antigorite content in serpentinized peridotite. These experimental earthquakes already led to the "dehydration driven stress transfer" (DDST) model, which suggests that a highly hydrated peridotite is not required when oceanic mantle events occur. A comparison of experimental and natural earthquake b-values implies that lower-plane peridotite is more hydrated beneath the Tohoku region, which could also explain the difference in oceanic-plate velocity structures near the trench identified in Ocean Bottom Seismometer studies off Tohoku and Hokkaido. These results suggest that lower-plane events occur in fresh peridotite near serpentinized faults.